Effects of Retention and Stability of Conventional Complete Dentures on Oral Health-Related Quality of Life - Urooj, Sara; Salman Ahmad; Aima Riaz; Afeera Rahat; Mahnoor Haroon; Rida Fatima (Pakistan Armed Forces Medical Journal, 2026)
Objective: To evaluate the impact of retention and stability of conventional complete dentures on oral health-related quality of life (OHRQoL). Study Design: Cross-Sectional Analytical Study. Place and Duration of Study: Foundation University College of Dentistry & Hospital, Islamabad, Pakistan, from May to Oct 2025. Methodology: A sample of 105 completely edentulous patients, 45–80 years old and rehabilitated with conventional full dentures, was included. Retention and stability of dentures were assessed with CU-modified Kapur criteria. The participants were divided into Group-1 (acceptable retention and stability) and Group-2 (unacceptable retention and stability). The Oral Impacts on Daily Performances (OIDP) scale was used to measure OHRQoL. Data were analyzed using the statistical significance of associations between variables and was tested at a p-value of 0.05. Results: Among the patients, 66(62.86%) were in Group-1 and 39(37.14%) were in Group-2. In comparison to patients with unacceptable retention (mean OIDP score: 15.43±5.87) and stability (mean OIDP score: 16.37±7.23), patients with acceptable denture mechanics reported significantly higher mean OHRQoL scores in Group-1(retention: 23.82±6.83; stability: 23.78±6.60) (p-value <0.001). Poor OHRQoL was significantly higher in Group-2 (58.97%) than in Group-1 (6.06%) (p-value <0.001). There was no association between gender and OHRQoL. Functional impairment was reported by most participants, especially in eating, speaking, and emotional well-being. Conclusion: Retention and stability of dentures contribute significantly to OHRQoL in older patients, thereby emphasizing the importance of careful prosthetic fabrication and follow-up.